2009
DOI: 10.1086/603640
|View full text |Cite
|
Sign up to set email alerts
|

The Life of a Dead Ant: The Expression of an Adaptive Extended Phenotype

Abstract: Specialized parasites are expected to express complex adaptations to their hosts. Manipulation of host behavior is such an adaptation. We studied the fungus Ophiocordyceps unilateralis, a locally specialized parasite of arboreal Camponotus leonardi ants. Ant-infecting Ophiocordyceps are known to make hosts bite onto vegetation before killing them. We show that this represents a fine-tuned fungal adaptation: an extended phenotype. Dead ants were found under leaves, attached by their mandibles, on the northern s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
203
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(207 citation statements)
references
References 25 publications
2
203
2
Order By: Relevance
“…1) (Andersen et al 2009;Pontoppidan et al 2009). Hirsutella citriformis could use of the host as a vehicle for dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…1) (Andersen et al 2009;Pontoppidan et al 2009). Hirsutella citriformis could use of the host as a vehicle for dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…B 371: 20150052 produce outcomes that are favourable to the microbe but not the host. For example, the fungal pathogen Ophiocordyceps unilateralis infects the nervous system of ants (Camponotus leonardi), leading the ants to attach themselves to leaves for several days until a fruiting body erupts from the ant's head, scattering fungal spores [67]. Other Ophiocordyceps species infect other species of Camponotus, and the ability to manipulate the ants' behaviour is unique to its naturally occurring pathogen [68,69].…”
Section: Role Of Microbes In Neural Mechanisms Of Foraging and Antiprmentioning
confidence: 99%
“…These interactions often occur as epizootics, contaminating a large number of ant specimens in small forest regions (Andersen et al 2009, Pontoppidan et al 2009). The possibility of acting directly and indirectly on the abundance of its hosts and, therefore, presenting an important function on communities' energy flow, makes studies on ant-fungi interactions highly recommended (Hudson et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed parasite-infected ants fixed through its mandibles to the abaxial veins of leaves, a behavior which is not apparent in healthy ants of this species. According to Andersen et al (2009), this behavior is adaptable to the fungus, ensuring a stable microclimatic niche for its development after the host's death and facilitating aerial dispersion of the spores. Araújo et al (2015) described three species of Ophiocordyceps that infect Camponotus ants, among them O. camponoti-atricipis, the target species of this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation